What patients and caregivers do with knowledge of Alzheimer's disease CSF test results: Findings from the IMPACT‐AD BC study. (20th December 2022) - Patel, Khushbu Jayeshkumar; Yang, David; Chambers, Colleen; Feldman, Howard H.; Hsiung, Ging‐Yuek Robin; Nygaard, Haakon B.; Best, John R.; Dwosh, Emily; Robillard, Julie M.; DeMarco, Mari L.
Abstract: Background: The growing clinical use of the analysis of CSF amyloid‐beta peptides and tau proteins to assist in the diagnosis Alzheimer's disease (AD) highlights an urgent need to understand the impact of this testing on patients, as well as their care partners. We aimed to address this knowledge gap by examining the perspectives of patients who underwent CSF AD biomarker testing as part of routine care, and a family member ('care partner'). Method: Within the 'Investigating the Impact of Alzheimer's Disease Diagnostics in British Columbia' (IMPACT‐AD BC) study (NCT05002699), we conducted semi‐structured telephone interviews with patients that meet the appropriate use criteria for AD CSF biomarker testing and separate interviews with their care partner. A subset of patients (n=33) and care partners (n=31) were interviewed post‐CSF biomarker disclosure and again ∼5 months (median: 4.9 [4.2‐5.3]) after the initial interview. Thematic content analysis was performed to understand the impact of AD biomarker testing on health behaviors, financial and care planning decisions, and resources and support needs. Result: Most patients (94%) rated their decision to undergo testing as "easy", with the remainder noting the decision was neither easy nor difficult. After result disclosure, a few patients (8%) reported feelings of concern, but the majority (80%) reported overall positive feelings from having more information about their brain health, certainty around their diagnosis, and the ability to plan ahead. Regarding actions patients planned to take after learning their test result, many expressed an intention to adopt or continue with healthy behaviors, such as exercise (42%). From the care partners' perspective, many expressed relief at having more diagnostic certainty post‐disclosure, and that this information would help them plan for future care needs. Post‐disclosure, care partners also relayed an increased awareness of future caregiving responsibilities and the need or desire to connect with community resources to help navigate this new role. Additional analyses investigated responses based on patients' amyloid status and disease severity. Conclusion: In summary, individuals undergoing AD CSF biomarker testing and their care partners found that CSF testing provided the information needed to help them make wellbeing decisions and plan their future.